Iron Doped Nanosheet-Assembled Ni3(NO3)2(OH)4 Spheres with Enhanced Photocatalytic Properties - Wang, Weiwei; Xu, Yingwei; Zhang, Aijuan; Li, Chengfeng (Asian Journal of Chemistry, 2015)
Iron ions play a critical, but yet unclear, role in improving the activity of Ni-based catalysts. To investigate the changes of iron ions doping in photocatalytic properties, we prepared undoped and Fe doped nanosheet-assembled Ni3(NO3)2(OH)4 spheres and particles by a simple hydrothermal method, which used urea to provide OH–. The effects of the iron ions and urea on the preparation of the Ni3(NO3)2(OH)4 structures were explored. In the presence of Fe, low concentration of urea favors the formation of Ni3(NO3)2(OH)4 particles, while high concentration prefers the formation of well-crystallized nanosheet-assembled Ni3(NO3)2(OH)4 spheres. Without Fe doping, only nanosheet-assembled Ni3(NO3)2(OH)4 spheres were obtained and more urea resulted in the formation of poor-crystallized Ni3(NO3)2(OH)4 spheres. Fe doped nanosheet-assembled Ni3(NO3)2(OH)4 spheres and particles with holes on the surface exhibited good photocatalytic activity in the degradation of methyl orange.